Cerebellar transcranial direct current stimulation disrupts neuroplasticity of intracortical motor circuits - Wei-Yeh Liao; Ryoki Sasaki; John G. Semmler; George M. Opie (PLoS ONE, 2022)
While previous research using transcranial magnetic stimulation (TMS) suggest that cerebellum (CB) influences the neuroplastic response of primary motor cortex (M1), the role of different indirect (I) wave inputs in M1 mediating this interaction remains unclear. The aim of this study was therefore to assess how CB influences neuroplasticity of early and late I-wave circuits. 22 young adults (22 ± 2.7 years) participated in 3 sessions in which I-wave periodicity repetitive transcranial magnetic stimulation (iTMS) was applied over M1 during concurrent application of cathodal transcranial direct current stimulation over CB (tDCSCB). In each session, iTMS either targeted early I-waves (1.5 ms interval; iTMS1.5), late I-waves (4.5 ms interval; iTMS4.5), or had no effect (variable interval; iTMSSham). Changes due to the intervention were examined with motor evoked potential (MEP) amplitude using TMS protocols measuring corticospinal excitability (MEP1mV) and the strength of CB-M1 connections (CBI). In addition, we indexed I-wave activity using short-interval intracortical facilitation (SICF) and low-intensity single-pulse TMS applied with posterior-anterior (MEPPA) and anterior-posterior (MEPAP) current directions. Following both active iTMS sessions, there was no change in MEP1mV, CBI or SICF (all P > 0.05), suggesting that tDCSCB broadly disrupted the excitatory response that is normally seen following iTMS. However, although MEPAP also failed to facilitate after the intervention (P > 0.05), MEPPA potentiated following both active iTMS sessions (both P < 0.05). This differential response between current directions could indicate a selective effect of CB on AP-sensitive circuits.